1996
DOI: 10.1128/mcb.16.10.5276
|View full text |Cite
|
Sign up to set email alerts
|

A Hierarchical Network of Interreceptor Interactions Determines Signal Transduction by Neu Differentiation Factor/Neuregulin and Epidermal Growth Factor

Abstract: The ErbB family includes four homologous transmembrane tyrosine kinases. Whereas ErbB-1 binds to the epidermal growth factor (EGF), both ErbB-3 and ErbB-4 bind to the Neu differentiation factors (NDFs, or neuregulins), and ErbB-2, the most oncogenic family member, is an orphan receptor whose function is still unknown. Because previous lines of evidence indicated the existence of interreceptor interactions, we used ectopic expression of individual ErbB proteins and their combinations to analyze the details of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
719
1
8

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 924 publications
(771 citation statements)
references
References 57 publications
(51 reference statements)
19
719
1
8
Order By: Relevance
“…Epiregulin-induced stimulation of tyrosine phosphorylation of ErbB-2 was weaker than that of EGF in SK-BR-3 and T47D cells, and HRG-a in T47D and MDA-MD-453 cells. NDF-induced heterodimerization of the receptors in cells that ectopically expressed ErbB receptors showed that the interaction between ErbB-3 and ErbB-2 is more extensive than the cross-talk between ErbB-4 and ErbB-2 (Tzahar et al, 1996). On the other hand, epiregulin bound directly to ErbB-4 but not ErbB-3 in four cell lines examined in the present study.…”
Section: Discussionmentioning
confidence: 43%
“…Epiregulin-induced stimulation of tyrosine phosphorylation of ErbB-2 was weaker than that of EGF in SK-BR-3 and T47D cells, and HRG-a in T47D and MDA-MD-453 cells. NDF-induced heterodimerization of the receptors in cells that ectopically expressed ErbB receptors showed that the interaction between ErbB-3 and ErbB-2 is more extensive than the cross-talk between ErbB-4 and ErbB-2 (Tzahar et al, 1996). On the other hand, epiregulin bound directly to ErbB-4 but not ErbB-3 in four cell lines examined in the present study.…”
Section: Discussionmentioning
confidence: 43%
“…ErbB2 is the preferred heterodimer partner of activated EGFR family members (Graus-Porta et al, 1997;Tzahar et al, 1996), and, when mutated, can inactivate other ErbB-family receptors (Qian et al, 1994). Therefore, we cannot rule out the possibility that in addition to inhibiting ErbB2 signaling, ErbB2DIC inactivates signaling by other members of the EGFR-family.…”
Section: Discussionmentioning
confidence: 99%
“…This is mediated by induction of EGFR/ErbB2 heterodimers (Spivak-Kroizman et al, 1992;Wada et al, 1990). Although each ligand-activated EGFR-family member can form a signaling dimer with most other members of this receptor family, ErbB2 is the preferred heterodimer partner (Graus-Porta et al, 1997;Tzahar et al, 1996). Moreover, ligand stimulated receptors compete for dimer formation with ErbB2 Karunagaran et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Both c-erbB3 and c-erbB4 bind a range of ligands of which the splice variants of neuregulin (heregulin, neu di erentiation factor) have received particular attention (Riese et al, 1995). Despite the absence of a direct ligand, transphosphorylation of c-erbB2 can be induced following heterodimerisation to ligand-bound c-erbB3 or c-erbB4 (Tzahar et al, 1996). c-erbB2 is the preferred partner for heterodimerization and when co-expressed with either EGFR or c-erbB3, synergistically enhances their mitogenic and transforming activity (Tzahar et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the absence of a direct ligand, transphosphorylation of c-erbB2 can be induced following heterodimerisation to ligand-bound c-erbB3 or c-erbB4 (Tzahar et al, 1996). c-erbB2 is the preferred partner for heterodimerization and when co-expressed with either EGFR or c-erbB3, synergistically enhances their mitogenic and transforming activity (Tzahar et al, 1996). Along with di erences in ligand binding each member of this sub-group has a di erent intrinsic tyrosine kinase activity i.e.…”
Section: Introductionmentioning
confidence: 99%